2018
DOI: 10.1007/978-3-030-05767-1_10
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Maintainability Prejudices with a Large-Scale Study of Open-Source Projects

Abstract: Exaggeration or context changes can render maintainability experience into prejudice. For example, JavaScript is often seen as least elegant language and hence of lowest maintainability. Such prejudice should not guide decisions without prior empirical validation. We formulated 10 hypotheses about maintainability based on prejudices and test them in a large set of open-source projects (6,897 GitHub repositories, 402 million lines, 5 programming languages). We operationalize maintainability with five static ana… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…On the one hand, the obtained results show that some patterns are aligned with results of some previous work where a significant difference in code quality regarding number of committers cannot be demonstrated [Norick, Krohn et al, 2010, Roehm, Veihelmann et al, 2019, Voulgaropoulou, Spanos et al, 2012. On the other hand, the correlation for other clusters was stronger as other work previously suggested [Perez-Castillo, Piattini et al, 2018].…”
Section: Figure 10: Scatter Plot With Clustering Distinction For Code Smells and Committerssupporting
confidence: 88%
See 1 more Smart Citation
“…On the one hand, the obtained results show that some patterns are aligned with results of some previous work where a significant difference in code quality regarding number of committers cannot be demonstrated [Norick, Krohn et al, 2010, Roehm, Veihelmann et al, 2019, Voulgaropoulou, Spanos et al, 2012. On the other hand, the correlation for other clusters was stronger as other work previously suggested [Perez-Castillo, Piattini et al, 2018].…”
Section: Figure 10: Scatter Plot With Clustering Distinction For Code Smells and Committerssupporting
confidence: 88%
“…[Voulgaropoulou, Spanos et al, 2012] draw similar conclusions after analysing various R statistical open-source systems. A more recent study by [Roehm, Veihelmann et al, 2019] rejected the hypothesis of code developed by a team has better quality than code developed by an individual, since the analysis thousands of GitHub repositories did not provide such evidence.…”
Section: Project Influence On Software Qualitymentioning
confidence: 99%
“…The reason is that both of these languages are object-oriented languages [2] and both of these belong to the C-family (e.g., C++, C#) [8]. Furthermore, an existing study DOI reference number: 10.18293/SEKE2021-152 concluded that Java projects have higher program comprehensibility compared to C, C++ and C# projects [9]. This study measures program comprehensibility using five static code metrics namely Too Long Files, Too Long Methods, Nesting Depth, Lack of Cohesive Comments (non-informative comments) and Duplicate Comments [9], [10].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, an existing study DOI reference number: 10.18293/SEKE2021-152 concluded that Java projects have higher program comprehensibility compared to C, C++ and C# projects [9]. This study measures program comprehensibility using five static code metrics namely Too Long Files, Too Long Methods, Nesting Depth, Lack of Cohesive Comments (non-informative comments) and Duplicate Comments [9], [10]. These metrics are language-independent and found to be a good indicator of program comprehensibility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation